New records of geometrid moths of the subfamily Larentinae (Lepidoptera: Geometridae) from the Amurskaya Oblast, Russian Far East - Aleksandr A. Kuzmin; Evgeniy A. Beljaev (Acta Biologica Sibirica, 2022)
An annotated list of 12 species of geometrid moths of the subfamily Larentiinae (Lepidoptera: Geometridae) found for the first time on the territory of Amurskaya Oblast, the Russian Far East, is given. There are: Brabira artemidora (Oberthür, 1884), Acasis bellaria (Leech, 1891), Trichopteryx polycommata ([Denis et Schiffermüller], 1775), Idiotephria debilitata (Leech, 1891), Idiotephria evanescens (Staudinger, 1897), Thera variata ([Denis & Schiffermüller], 1775), Ecliptopera umbrosaria (Motschulsky, 1861), Triphosa dubitata (Linnaeus, 1758), Triphosa sericata (Butler, 1879), Operophtera relegata Prout, 1908, Hydrelia parvulata (Staudinger, 1897), and Venusia semistrigata (Christoph, 1881). From them, for 9 East Asian species these finds strongly expand to north-west their previously known areas.